2009
DOI: 10.1063/1.3233944
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic properties of Bi(Fe0.95Co0.05)O3 ceramics

Abstract: Articles you may be interested inEffect of Pr-and Nd-doping on structural, dielectric, and magnetic properties of multiferroic Bi0.8La0.2Fe0.9Mn0.1O3Structure and multiferroic properties of Bi(1-x)DyxFe0.90Mg0.05Ti0.05O3 solid solution Influence of A-site doping on structural properties of Bi0.95Pr0.05FeO3 multiferroics AIP Conf.Bi͑Fe 0.95 Co 0.05 ͒O 3 bulk ceramics were prepared by rapid sintering using sol-gel derived fine powders. Bi͑Fe 0.95 Co 0.05 ͒O 3 crystallized in a rhombohedrally distorted BiFeO 3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 17 publications
4
58
0
1
Order By: Relevance
“…Efforts have been paid to improve the magnetization of BiFeO 3 to get a great response to the application of magnetic field. Xu et al reported that Co substitution could enhance the magnetic properties of BiFeO 3 ceramics [9]. However, Co doping effects on magnetic properties of BiFeO 3 with sol-gel method remain as an open issue.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been paid to improve the magnetization of BiFeO 3 to get a great response to the application of magnetic field. Xu et al reported that Co substitution could enhance the magnetic properties of BiFeO 3 ceramics [9]. However, Co doping effects on magnetic properties of BiFeO 3 with sol-gel method remain as an open issue.…”
Section: Introductionmentioning
confidence: 99%
“…14 Significant increase in magnetization has been found in BiFe 0.95 Co 0.05 O 3 bulk ceramics as compared to the case of pure BFO samples prepared by rapid sintering using solgel derived powders. 15 16 Decrease in the particle size resulting in significant increase in the magnetic properties, may be due to the suppression of the spin spiral structure of periodicity 62 nm. 17 The magnetic properties in these nanosized particles greatly depend on the morphology and experimental conditions and indirectly on the preparation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports suggest that the use of transition metals in BiFeO 3 is beneficial to increase the ferromagnetic character [11]. Possible explanations for the increase in magnetization when doping with cobalt, are the super-exchange interaction between Fe 3+ and Co 3+ [12], the spin-glass behavior of BiFeO 3 [13], and an increase in spin canting due to lattice strain [14]. However, the direct effect of cobalt remains unclear due to lack of purity of materials reported in the literature.…”
Section: Introductionmentioning
confidence: 97%